THE FOOD CULTURE OF ESTONIAN STAROVERY (OLD BELIEVERS): TRADITIONS AND THE PRESENT - Kõivupuu, Marju (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2012)
The Russian Starovery are a time-honoured minority in Estonia, having migrated to the western coast of Lake Peipsi from central Russia at the end of the 17th century. The Russian Starovery subsisted mainly on fishing the lakes of Peipsi, Võrtsjärv, Viljandi, and Ladoga, as well as the Gulf of Riga. Besides, they grew chicory, cucumbers, and onions on their small garden plots and worked as masons in Estonian towns and rural areas. During the Soviet era, the Old Believers sold most of their home-grown vegetables to Russia, mainly Leningrad (Petersburg). After Estonia regained independence, the Union of the Estonian Old Believers’ Congregations was also restored in 1995, and in the new economic situation the Old Believers began to look for new ways of earning a living. In addition to road-villages, museums of local history, and chapels, the fish and onion restaurant opened at Kolkja in 1999 has become a central attraction for tourists, allowing them to get acquainted with the Old Believers’ daily culture, including food culture. The author analyzes self-representation and entrance of the Russian Starovery into reindependent Estonia through food culture, dwelling on theoretical presumption that food-culture and eating is an intergral part of human culture. The basis for generalisations is gathering of heritage related to food culture from the Russian Starovery, as well as printed materials and websites where they introduce themselves through food culture. It is indeed noteworthy that the Starovery´s villages along Lake Peipsi are advertised in media and tourism booklets primarily through their characteristic food culture, although the Old Believers’ cuisine – regardless of the religious convictions that have shaped their eating habits – constitutes a mixture of both Estonian (and thereby also Baltic German) and Russian rural and urban food traditions.